Reinforcement Learning With Parsimonious Computation and a Forgetting Process - Toyama, Asako; Katahira, Kentaro; Ohira, Hideki (Frontiers in Human Neuroscience, 2019)
Decision-making is assumed to be supported by model-free and model-based systems: the model-free system is based purely on experience, while the model-based system uses a cognitive map of the environment and is more accurate. The recently developed multistep decision-making task and its computational model can dissociate the contributions of the two systems and have been used widely. This study used this task and model to understand our value-based learning process and tested alternative algorithms for the model-free and model-based learning systems. The task used in this study had a deterministic transition structure, and the degree of use of this structure in learning is estimated as the relative contribution of the model-based system to choices. We obtained data from 29 participants and fitted them with various computational models that differ in the model-free and model-based assumptions. The results of model comparison and parameter estimation showed that the participants update the value of action sequences and not each action. Additionally, the model fit was improved substantially by assuming that the learning mechanism includes a forgetting process, where the values of unselected options change to a certain default value over time. We also examined the relationships between the estimated parameters and psychopathology and other traits measured by self-reported questionnaires, and the results suggested that the difference in model assumptions can change the conclusion. In particular, inclusion of the forgetting process in the computational models had a strong impact on estimation of the weighting parameter of the model-free and model-based systems.